Effect of Chain Branching on Orientational Ordering in Glycolipid Self-assembly by 2H-NMR using Extrinsic Probes. (2018) - Idayu Zahid, N.; Anwar Ishak, Khairul; Timimi, Bakir A.; Hashim, Rauzah
Abstract: The structure and dynamics of molecular solids, liquid crystals, and thin films of membrane lipids may be elucidated from the use of deuterium NMR ( 2 H-NMR) spectroscopy. The 2 H-NMR spectrum of a deuterated material (either selectively or fully) is rather simpler to interpret compared with the corresponding proton NMR ( 1 H-NMR). Here, we apply this technique to understand the effect of chain branching on orientational order of the glycolipid self-assembly by using deuterated probes. The 2 H-NMR resonance of n -octanol-d17 in n -octyl- β -D-glucopyranoside ( β -GlcOC8 ) and the branched-chain glycolipid 2 -hexyldecyl- β -D-glucopyranoside ( β -GlcOC10 C6 ) were measured at different temperatures. We also measured the 2 H-NMR spectrum of 2 -ethyl- n -hexanol- α, α -d2, a branched-chain alcohol which is selectively deuterated at α -position in β -GlcOC8 . All systems gave quadrupolar splittings in their respective 2 H-NMR spectra, which are attributed to the formation of anisotropic phase. The n -octanol-d17 dissolved in β -GlcOC8 give us spectra in the lamellar phase and when used with a branched-chain lipid, i.e. β -GlcOC10 C6, gave us new spectra in the inverse hexagonal phase. The magnitude of the quadrupolar splittings of the n -octanol-d17 is indicative of the degree of orientational ordering in the given system. The results show that the quadrupolar splitting is larger in β -GlcOC8 lipid than in β -GlcOC10 C6 .